DNA copy number changes define spatial patterns of heterogeneity in colorectal cancer - Soulafa Mamlouk (Nature Portfolio, 2017)
The contribution of intra-tumour heterogeneity is increasingly associated with resistance to therapy. Here, the authors use genomic analyses to study heterogeneity in colorectal cancer and perform in-depth reconstruction of heterogeneity in one sample.